Should acellular pertussis vaccine be recommended to healthcare professionals? - José Cassio de Moraes; Telma Carvalhanas; Lucia Ferro Bricks (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The aim of this study was to describe recent changes in the epidemiology of pertussis and existing policies regarding recommended and mandatory occupational vaccinations for healthcare professionals (HCPs). The authors carried out an extensive review of references on the PubMed and SciELO databases and the official sites of the World Health Organization, Pan American Health Organization, Centers for Disease Control and Prevention, and Brazilian Ministry of Health, using the keywords pertussis, vaccines and healthcare professionals. Vaccination against pertussis is recommended for HCPs in the United States, Canada, nine European countries, Australia, Hong Kong, Singapore, Costa Rica, Argentina and Uruguay, and in some countries it is compulsory. In Brazil, only one publication discussing the risk of pertussis among HCPs was found. Considering the reemergence of pertussis and the great number of associated hospitalizations and deaths registered in 2011, it is necessary to review public policies regarding HCP pertussis vaccination, particularly among workers in frequent contact with young babies.